Photosynthetic Temperature Tolerance Threshold Determines How Isoprene Emission is Affected by Elevated CO2 Concentration at High Temperatures - Souza, Vinícius Fernandes; Gonçalves, José Francisco de Carvalho; Rasulov, Bakhtier; Talts, Eero; Morfopoulos, Catherine; Junior, Sérgio Duvoisin; Albuquerque, Patrícia Melchionna; Niinemets, Ülo (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT The suppression of isoprene emissions by high CO2 levels can be mitigated by increasing temperature; however, little is known about why and to what extent species differ in their temperature‐dependent release from high CO2 inhibition. We studied leaf photosynthetic characteristics and isoprene emissions over a 25°C–40°C temperature range at CO2 concentrations of 150, 400, and 1000 μmol mol−1 in two species with contrasting heat resistance. In the temperate species Populus tremula, rising temperatures above 30°C shifted electron flow from photosynthesis to isoprene synthesis, reducing CO2 inhibition due to enhanced isoprene synthase activity and decreased sensitivity of the DMADP pool. Conversely, the tropical species Inga edulis showed greater heat tolerance in its photosynthetic apparatus, maintaining electron flow for CO2 fixation, and exhibited a consistent CO2 suppression of isoprene emissions throughout the experiment. These findings indicate that species differences in relative sensitivity of light and dark reactions of photosynthesis play crucial roles in modulating isoprene emissions under combined high CO2 and temperature conditions.